PENGAWETAN DUA PULUH JENIS KAYU IRIAN JAYA SECARA RENDAMAN PANAS-DINGIN - Sasa Abdurrohim; Abdurahim Martawijaya (Jurnal Penelitian Hasil Hutan, 1987)
Twenty  wood species obtained from  Irion Joya measuring 5 x 5 x 60 cm were treated by hot and cold soaking  using BFCA preservative  with 5 and  10 percent  of  solution  concentration.   Hot   immersion  period   was kept  for 1 hour,  2 hours  and  3 hours, with  temperature range  of 60°C-70°C,  followed   by cold immersion for 24 hours.The test result of the twenty wood species, after taking both penetration and retention  requirements  into consideration for  wood uses under roof,  and in the open air both  without  soil contact,  showed  that two  wood species among  them i.e. nifoek  (Eucalyptus  deglupta  Bl.) and seriega (Eugenia  sp.),  could  not  be satisfactorily   treated  under  the experimental  conditions.   The other eighteen species could be treated  by either one, several,  or all treating schedules  employed  in this research. Nevertheless,   it is important   to note  that  two  of  the eighteen  species,  i.e. sougwa (Palaquium  multiflorum)  and matoa (Pometia  pinna ta Forst.) fulfilled the requirements for  wood usage under the roof  only  without  soil contact. The preservation  schedule proposed  for  the eighteen  wood species is presented  in Table 4.